Raising efficiency and effectiveness in scholarly communication: an example of the Bridge of Knowledge platform at Gdańsk University of Technology (Pubmet, 2022)
Current concerns about scholarly communication activities highlight its complexity (Baffy et al., 2020). Researchers need support in many areas, such as in disseminating research findings (both publications and research data) openly, in promoting scientific output, or in preparing data management plans (DMPs). Scholarly communication is constantly evolving by introducing new avenues such as Plan S, open peer review, or data citations shaping the academic environment and researchers’ recognition and prestige.Changes in scholarly communication and difficulties caused by COVID-19 had given rise to new dissemination channels, openness in publishing results, and discussion between researchers, publishers, funders, or librarians on modern scholarly communication practices (Cuevas Shaw, 2021).To keep up with these changes in the scholarly communication landscape, the Gdańsk University of Technology (Gdańsk Tech) Library had actively been involved in two projects that raised effectiveness and efficiency in sharing and disseminating research findings. The first project was the Multidisciplinary Open System Transferring Knowledge. The acronym of its name in the Polish language is “MOST Wiedzy”, which means “the bridge of knowledge”, and its primary objective was to introduce openaccess infrastructure to the academic community (Wałek & Lubomski, 2017). The second project – the Bridge of Data – was established to support researchers in managing different layers of research data. All our websites and services are available through the MOST Wiedzy platform. The project was unique in this part of Central and Eastern Europe and included launching of the Open Science Competence Centre as part of the Gdańsk Tech Library.With a strong infrastructure composed of a current research information (CRIS) system, repositories (publications, OA publications, and research data), and scholarly support services we were able to establish a platform for managing and promoting scientific output. This platform develops with shifts in the scholarly communication environment (such as Plan S, evaluation units, and academic ranking), and we handle the challenges of open science and intellectual property rights as they emerge, shaping and guiding our platform’s further development. Working with and for researchers, the Gdańsk Tech Library seeks to tailor its infrastructure to meet new needs. At the same time, our Competence Centre offers customized services to upgrade research, digital, and information skills through webinars, training, interactive knowledge hubs, or professional working groups, and networking to improve the use of available infrastructure (e.g. we teach researchers how to fill in metadata).The aim of our study is to review scholarly communication support provided by the Gdańsk Tech Library. We will first identify the main scholarly communication activities (e.g., creation, publication, dissemination, and discovery of academic research, applying for research funding, writing DMPs, cross-checking requirements of Plan S, assessment & impact metrics) and then map the process against provided support and infrastructure (e.g. institutional repository, research data repository, training, copyright service). In addition, we will invite authors to identify areas that still need support and improvement. Our findings, we hope, will help to understand changes in scholarly communication and the supporting role of a modern library. Building support infrastructure and being part of cultural change toward openness in science may be challenging but is highly rewarding and far-reaching.